Politics and Corporate‐Sector Environmentally Significant Actions: The Effects of Political Partisanship on U.S. Utilities Energy Efficiency Policies - Adua, Lazarus; Clark, Brett (The Review of policy research, 2021)
This study assesses the direct, indirect, and total impacts of political partisanship on state‐level utilities' investment in energy efficiency. This subject is of utmost importance because energy efficiency improvement has become a linchpin in worldwide efforts to combat climate change and other environmental challenges. Analysis of data on 51 electric utilities nested within 31 U.S. states indicates that political partisanship influences utilities' energy efficiency policies. There is strong evidence that electric utilities in states dominated by the Republican Party are less likely to invest in energy efficiency than those in states governed by the Democratic Party. This finding suggests that political partisanship may be shaping the policy and regulatory frameworks put in place by state governments to incentivize or compel the participation of private‐sector entities' in environmental management and/or resource conservation. Este estudio evalúa los impactos directos, indirectos y totales del partidismo político en la inversión de las empresas de servicios públicos a nivel estatal en eficiencia energética. Este tema es de suma importancia porque la mejora de la eficiencia energética se ha convertido en un eje de los esfuerzos mundiales para combatir el cambio climático y otros desafíos ambientales. El análisis de los datos de 51 empresas eléctricas ubicadas en 31 estados de EE. UU. Indica que el partidismo político influye en las políticas de eficiencia energética de las empresas. Existe una fuerte evidencia de que las empresas eléctricas en los estados dominados por el Partido Republicano tienen menos probabilidades de invertir en eficiencia energética que las de los estados gobernados por el Partido Demócrata. Este hallazgo sugiere que el partidismo político puede estar dando forma a los marcos normativos y regulatorios establecidos por los gobiernos estatales para incentivar u obligar la participación de entidades del sector privado en la gestión ambiental y / o conservación de recursos. 本研究评估了政治派别对州级公用事业在能源效率上的投资产生的直接、间接以及全部影响。该主题至关重要，因为能源效率的提升已成为全球为应对气候变化及其他环境挑战所作努力的最重要部分。关于31个州内51个电力事业的数据分析表明，政治派别会影响公用事业的能源效率政策。有力证据表明，相比民主党州，共和党州的电力事业更不可能在能源效率上投资。研究发现暗示，政治派别可能会影响由州政府制定的政策和监管框架，以期激励或强制私人部门实体参与环境管理和/或资源节约。